Cancer Stem Cell DNA Enabled Real‐Time Genotyping with Self‐Functionalized Quantum Superstructures—Overcoming the Barriers of Noninvasive cfDNA Cancer Diagnostics. Issue 4 (4th March 2022) - Haldavnekar, Rupa; Ganesh, Swarna; Venkatakrishnan, Krishnan; Tan, Bo
Abstract: Cancer diagnosis and determining its tissue of origin are crucial for clinical implementation of personalized medicine. Conventional diagnostic techniques such as imaging and tissue biopsy are unable to capture the dynamic tumor landscape. Although circulating tumor DNA (ctDNA) shows promise for diagnosis, the clinical relevance of ctDNA remains largely undetermined due to several biological and technical complexities. Here, cancer stem cell‐ctDNA is used to overcome the biological complexities like the inability for molecular analysis of ctDNA and dependence on ctDNA concentration rather than the molecular profile. Ultrasensitive quantum superstructures overcome the technical complexities of trace‐level detection and rapid diagnosis to detect ctDNA within its short half‐life. Activation of multiple surface enhanced Raman scattering mechanisms of the quantum superstructures achieved a very high enhancement factor (1.35 × 10 11 ) and detection at ultralow concentration (10 −15 M) with very high reliability (RSD: 3–12%). Pilot validation with clinical plasma samples from an independent validation cohort achieved a diagnosis sensitivity of ≈95% and specificity of 83%. Quantum superstructures identified the tissue of origin with ≈75–86% sensitivity and ≈92–96% specificity. With large scale clinical validation, the technology can develop into a clinically useful liquid biopsy tool improving cancer diagnostics. Abstract : Here, cancer stem cell circulating DNA is used to overcome the biological complexities related to the tumor heterogeneity. Ultrasensitive quantum superstructures enable trace‐level detection overcoming technical complexities of trace‐level detection and rapid diagnosis to detect circulating tumor DNA (ctDNA) within its short half‐life. Pilot validation with clinical plasma samples achieve a diagnosis sensitivity of ≈95% and specificity of 83%. Quantum superstructures identifies the tissue of origin with ≈75–86% sensitivity and ≈92–96% specificity.